2020
DOI: 10.2196/preprints.22327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Picture Is Worth a Thousand Views: A Triple Crossover Trial of Visual Abstracts to Examine Their Impact on Research Dissemination (Preprint)

Abstract: BACKGROUND The visual abstract is a graphic summary of a research article’s question, methods and major findings. Though they have a number of uses, they are chiefly used to promote a research article on social media. OBJECTIVE To determine if the use of visual abstracts increases the visibility of nephrology research shared on Twitter. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…2 Felszeghy et al used a Kahoot gamification program for teaching histology to medical and dental students and concluded that the learning process and participant satisfaction can be significantly improved by introducing Kahoot-based gamification programs in histology courses. 3 Other similar quiz-based gaming applications available are Socrative, Doctor's Dilemma, Quizizz, Quiz maker, Lesson up, Quizlet, and Canvas. 'Ghost mode' on Kahoot allows students to compete against their first attempt to improve their time.…”
Section: Student Feedback On the Use Of Gamification For Teaching Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Felszeghy et al used a Kahoot gamification program for teaching histology to medical and dental students and concluded that the learning process and participant satisfaction can be significantly improved by introducing Kahoot-based gamification programs in histology courses. 3 Other similar quiz-based gaming applications available are Socrative, Doctor's Dilemma, Quizizz, Quiz maker, Lesson up, Quizlet, and Canvas. 'Ghost mode' on Kahoot allows students to compete against their first attempt to improve their time.…”
Section: Student Feedback On the Use Of Gamification For Teaching Pat...mentioning
confidence: 99%
“…Since the introduction of this idea in 2016, the concept of VA is being increasingly used by scientific journals, academic conferences and even health magazines to boost visibility of their literary content. 3 This has become even more relevant during the Covid-19 pandemic when virtual-learning platforms including e-education models have been promoted as effective modalities to disseminate continuing medical education and journalistic content. 4 VA provides a concise visual summary to help readers scan and find the most relevant content for them.…”
mentioning
confidence: 99%